Enhancement of Corrosion Resistance in Steam Turbines Blades Using Nanoparticles Coatings - Bedaiwi, Bashar Owaid; Abd, Abeer Kadhum (Al-Nahrain Journal for Engineering Sciences, 2017)
Corrosion in turbine blades may be considered the most crucial problems in power plants. Corrosion may lead to unbalance masses in turbine blades and therefor serious vibration problems. In this study coating nanomaterials namely Al2O3 and TiO2 are used to resist the corrosion. Coatings consist of Al2O3 with 13 wt% TiO2 are generally used to improve the corrosion, erosion and wear resistance. Tests specimens were taken from the portion of turbine blades in Al-Doura station which located in the south of Baghdad. The specimens are divided into two groups, the first group without coating and the second group with nanoparticale coating including alumina (Al2O3) and (Al2O3-13 % wt TiO2), the coating applying by airbrush device using atomization technique with the aid of nitrogen 2 bar pressure . The properties of coated specimens have been investigated by SEM. The SEM showed that the deposition of nanoparticles on the surface of the samples was uniform and homogeneous. The thickness of coated layers was obtained using gravimetric method. Nano alumina with 13% wt of Titanum oxide coating gave the highest thickness 7.1 µm because of agglomeration of these particles comparing with other particales. Electrochemical properties was achieved by corrosion test at 90 ° for 20 min, the properties indicated that the corrosion resistance increased for coated specimens and these properties showed that the nano alumina with 13% wt of nano Titanium oxide was better than other coating and get a protection efficiency equal to 85.56%.